2008
DOI: 10.1192/apt.bp.107.004499
|View full text |Cite
|
Sign up to set email alerts
|

What can the science of well-being tell the discipline of psychiatry – and why might psychiatry listen?

Abstract: There is a field of knowledge that speaks of the promotion of positive mental health, well-being and happiness yet it may not be well-known to all psychiatric practitioners. Economists, geneticists, positive psychologists, evolutionary psychologists, neuroscientists and sociocultural researchers have all contributed to what might be termed the emerging science of well-being. This article prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In summary, 87 distinct studies were identified. The ten elaborating papers included in the thematic analysis but not in the vote counting were papers 11,15,16,19,26,48, 50, 53, 71 and 73 in online Table DS1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, 87 distinct studies were identified. The ten elaborating papers included in the thematic analysis but not in the vote counting were papers 11,15,16,19,26,48, 50, 53, 71 and 73 in online Table DS1.…”
Section: Resultsmentioning
confidence: 99%
“…First, it allows available evidence to be more easily identified. A recovery orientation has overlap with the literature on well-being, 26 positive psychology 27 and self-management, 28 and systematic reviewing is hampered by the absence of relevant MeSH (Medical Sub-Headings) headings relating to recovery concepts. The coding framework provides keywords for use when undertaking secondary research, and the identification of related terms provides a taxonomy which will be useable in reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Wellbeing is a concept used increasingly across a range of disciplines and has implications for expanding how we consider men’s subjectivities. However, the term is used in diverse and conflicting ways to conceive of subjectivity and the social, and it currently lacks conceptual clarity (Hanlon and Carlisle 2008). In popular media discourse, whereas wellbeing was previously used to describe the ‘body politic’, by the mid‐1980s the move was towards identifying and pursuing valued individual attributes through personal practices (Sointu 2005).…”
Section: Wellbeing and Menmentioning
confidence: 99%